Gending Rare Dalam Perspektif Pendidikan Agama Hindu - Ni Wayan Yuni Astuti (Jayapangus Press, 2020)
The entry of foreign cultures is unstoppable. This of course has a positive and negative impact. Not all foreign cultural values ​​must be shunned, but if foreign culture has positive values ​​it should be accepted and adapted to Indonesian culture. Some positive foreign cultures, for example: a culture of respecting time, a culture of independent living, discipline, and hard work and so on. This positive impact should be accepted and applied in various forms of life. The influence of foreign cultures that are not relevant to the culture of the Indonesian people, of course, has more negative impacts than positive ones. The foreign culture that is not in harmony can be seen in the habits of the people. one of the local cultures in Bali, namely Gending Rare which is almost extinct and is no longer visible, therefore it is necessary to explore the culture again by exploring the noble values ​​that exist in the Gending Rare through research. In this study, the theories used to solve research problems are Humanistic Theory, Structural Functionalism Theory, and Behavioristic Education Theory. Data collected using the library method. After the data was collected, the data were analyzed descriptively qualitatively. The teaching contained in Gending Rare is the Teaching of Asih, which is a family attitude that is not individuality that needs to be nurtured from childhood, so that children as adults have strong attitudes and mentality in facing temptations and challenges. Manifesting this kind of attitude should create mutual affection and love and mutual respect in life, and the teaching of Bhakti. The Hindu Religious Education Values ​​contained in Gending Rare are Divine Values, Ethical Values, and Aesthetic Values.